Implementasi Securities Crowdfunding di LBS Urun Dana berdasarkan POJK 57/2020 dan Fatwa DSN-MUI 140/2021 - Mohamad Kharis Umardani; Amir Mahmud; Tresia Elda (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the implementation of Securities Crowdfunding (SCF) in Indonesia, particularly Sharia-based SCF conducted through the LBS Urun Dana platform under OJK Regulation No. 57/POJK.04/2020 and DSN-MUI Fatwa No. 140/DSN-MUI/VIII/2021. The research addresses the limited regulatory and operational studies concerning Sharia SCF practices in Indonesia’s digital capital market. This study aims to analyze the legal framework governing SCF and evaluate the implementation of Sharia-compliant SCF mechanisms in practice. The research employs a normative-empirical method using statutory, conceptual, and case approaches. Data were collected through literature studies and in-depth interviews with parties involved in SCF implementation. The findings indicate that POJK No. 57/POJK.04/2020 has provided a broader legal basis for fundraising through equity, debt securities, and sukuk-based crowdfunding. Meanwhile, DSN-MUI Fatwa No. 140/2021 strengthens Sharia compliance in SCF activities. The study also finds that the implementation of Sukuk Musyarakah by PT Sinergi Nusantara Sentosa through LBS Urun Dana reflects the practical application of Sharia principles in financing real-sector projects transparently and efficiently.